2013
DOI: 10.30955/gnj.000372
|View full text |Cite
|
Sign up to set email alerts
|

PM10-PM2.5 time series and fractal analysis

Abstract: Several epidemiological studies have shown an association between particulate air pollution and health effects. Suspended particulates and more specifically the inhalable PM 10 fraction appear to cause respiratory health effects and heart diseases. Furthermore, particulate pollution is of paramount importance in areas with open-pit mines and especially when it is combined with raw lignite transfer and combustion in power stations through the suspension of particles and stack emissions, respectively. The penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…All these are factors affecting the concentrations levels of PM of the region. A previous study conducted by Evagelopoulos et al (2006) analyzed the PM10 and PM2.5 concentrations and the ratios of PM2.5/PM10 based on PM measurements derived by a monitoring station located at Aristotelous square in the city of Kozani [5]. They found that the average PM2.5/PM10 ratio was 0.42±0.1 indicating that coarser particles are dominant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these are factors affecting the concentrations levels of PM of the region. A previous study conducted by Evagelopoulos et al (2006) analyzed the PM10 and PM2.5 concentrations and the ratios of PM2.5/PM10 based on PM measurements derived by a monitoring station located at Aristotelous square in the city of Kozani [5]. They found that the average PM2.5/PM10 ratio was 0.42±0.1 indicating that coarser particles are dominant.…”
Section: Resultsmentioning
confidence: 99%
“…Also, they found that the ratios exhibited diurnal and seasonal variability revealing the contribution of meteorological parameters (e.g. precipitation) and anthropogenic activities [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation